2012
DOI: 10.1080/10256016.2012.661731
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes determination in some Romanian wines

Abstract: This paper presents a study concerning the isotopic fingerprint ((18)O and (13)C) of some wines prepared from relevant Romanian grape varieties (e.g. Feteasca Alba (FA), Feteasca Regala (FR) and Cabernet Sauvignon (CS)) obtained in different vintage years (2002, 2003, 2004, 2007 and 2008). These wines were obtained from different vineyards having a significant role in the wine market: Cotesti, Tohani, Stefanesti, Aiud, Cotnari, Bucium, Murfatlar, Bujoru, Dragasani and Valea Calugareasca. Several observations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…As some of these samples (from Austria and Slovenia) are the official ones for the EU wine database, which were harvested in selected vineyards by governmental collectors and vinified applying a standardized protocol, an assignment to a certain area, locality, or winery was not done to retain data confidentiality. The Romanian samples come from only two of the wine producing regions, Oltenia and Muntenia, both located in the very south of Romania (Magdas et al, 2012) and, therefore, do not represent the isotopic variation of the entire Romania, which is significantly larger (see Magdas et al, 2012). The Montenegrin wine samples come from "13.…”
Section: Wine Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As some of these samples (from Austria and Slovenia) are the official ones for the EU wine database, which were harvested in selected vineyards by governmental collectors and vinified applying a standardized protocol, an assignment to a certain area, locality, or winery was not done to retain data confidentiality. The Romanian samples come from only two of the wine producing regions, Oltenia and Muntenia, both located in the very south of Romania (Magdas et al, 2012) and, therefore, do not represent the isotopic variation of the entire Romania, which is significantly larger (see Magdas et al, 2012). The Montenegrin wine samples come from "13.…”
Section: Wine Regionsmentioning
confidence: 99%
“…As the weather conditions play such a fundamental role for the isotope pattern of wine, the year of harvest is important since the weather varies from year to year (e.g., Christoph et al, 2003Christoph et al, , 2015Magdas et al, 2012;Philipp et al, 2018). The investigation of wine harvested in 2008 and 2009 is of relevance for wine control, as (I) wine is a commodity that is not only consumed as young wine, but also as aged wine, with the (suitable) aged wine becoming more esteemed and, thus, expensive, and (II) the environmental conditions do vary from year to year, but similarities between certain years are usually found (e.g., coldhumid vs. hot-dry weather) and, thus, past vintages show ranges of variations between years, relevant for control of wine without vintage information.…”
Section: Introductionmentioning
confidence: 99%
“…A range of analytical methods have been developed to address this issue. The stable isotope ratio method has already shown its applicability to solve the authenticity problems of milk products [2,3,4,5,6,7,8], beef [9,10,11], olive oil [12,13], honey [14,15], wine [16], and juices [17]. Ehtesham et al [18] showed that the δ 2 H and δ 13 C of four fatty acids and bulk milk powder were found to be correlated with regional production area in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of stable isotopes ( 2 Н, 13 С, 18 О) is currently the official and stan dard method for determining the authenticity of many foods and beverages, including wine products [29][30][31]. Recently, however, alternative innovative methods for food control began to appear; one of them is NMR spectroscopy [32][33][34]. NMR coupled with multivariate data analysis is used to control grape varieties, geo graphical origin, and vintage of wines [34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%